Ribosomal DNA probe for differentiation of Babesia microti and B. gibsoni isolates. - Conrad, P A (1992)
The objective of this study was to determine whether different isolates of Babesia microti could be distinguished from morphologically similar isolates of B. gibsoni by using a ribosomal DNA (rDNA) probe. A Babesia-specific rDNA probe was obtained by polymerase chain reaction amplification of sequences from B. microti DNA using universal primers directed against highly conserved portions of the eukaryotic 16S-like rRNA gene. The chemiluminescent rDNA probe hybridized to Southern blots of restriction endonuclease-digested DNA preparations of different isolates of B. gibsoni from infected dogs and B. microti from infected humans and white-footed mice. Restriction fragment length polymorphisms served to differentiate these species. Although the hybridization patterns seen with DNAs from six B. microti isolates did not vary, those of the five B. gibsoni isolates did indicate genotypic variation. We concluded that isolates of B. microti and B. gibsoni can be differentiated on the basis of restriction fragment length polymorphism detected with a chemiluminescent rDNA probe.